Summerhill: seeds of democracy in Canada - O’Rourke, Deb (Revista Hipótese, 2017)
In Canada and the US, A. S. Neill’s 1960 book on Summerhill inspired the Free School Movement, in which hundreds of grassroots schools were created by parents, teachers and students. In Canada, public alternative schools were created to ensure that all economic classes could have access to different education models, but very few free schools have survived the systemic pressures. ALPHA Alternative School includes parents in the democratic partnership and relies on their advocacy. The author sees Summerhill as a vital role-model, not only for education that fosters “strong individuals and community persons,” but for feisty school communities struggling to survive and, in the process, draw their nations further along the spectrum from idealized to actualized democracy.